Disentangling family firm heterogeneity: Evidence from a cross-country analysis - Arteaga, Rocio; Basco, Rodrigo (European Journal of Family Business, 2023)
The existing typologies, classifications that identify types of family firms based on specific characteristics, aim to enhance our understanding of the heterogeneity of family businesses. However, these typologies fall short in thoroughly exploring and predicting behavioural and performance consequences associated with being categorized within specific classifications. Furthermore, the majority of the existing analyses have been empirically tested in one single country. To address these two research gaps, we use a sample of 814 small- and medium-sized family firms operating in 21 countries, collected by the STEP Project Global Consortium. This sample is employed to classify family firms based on their corporate governance similarities and explore their behavioural and performance patterns. Building on the principles of the configurative approach, we find that each of the four family firm configuration—group of family firms with related corporate governance mechanisms—has a unique yet similar combination of patterns in terms of transgenerational entrepreneurship practices, non-economic goals, and firm performance. Additionally, expanding on the isomorphic effect, we find evidence indicating that certain world macroregions exhibit a greater propensity for specific corporate governance configurations compared to others.